2015
DOI: 10.1161/atvbaha.115.306102
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen-Related Receptor γ Plays a Key Role in Vascular Calcification Through the Upregulation of BMP2 Expression

Abstract: Objective-Vascular calcification which refers to ectopic mineralization in vascular cells is associated with several conditions, such as chronic kidney disease, atherosclerosis, and diabetes mellitus. Estrogen-related receptor (ERR)γ is a member of the orphan nuclear receptor superfamily, which plays diverse roles in regulating homeostatic and metabolic processes. However, the role of ERRγ in vascular calcification has not been investigated to date. The aim of the present study was to examine the role of ERRγ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
24
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 30 publications
2
24
0
Order By: Relevance
“…48,49 The estrogen receptor-related receptors have a demonstrated role in promoting VSMC mineralization and bone formation and hence may be prime candidates for further investigation of these pathways with specific antagonist or silencing studies. 50,51 Interestingly, we found that E2 had site-specific effects on both calcification and ERβ expression. E2 increased plaque calcification and decreased ERβ expression in the aortic sinus but not the innominate artery, in both male and female animals.…”
Section: Discussionmentioning
confidence: 74%
“…48,49 The estrogen receptor-related receptors have a demonstrated role in promoting VSMC mineralization and bone formation and hence may be prime candidates for further investigation of these pathways with specific antagonist or silencing studies. 50,51 Interestingly, we found that E2 had site-specific effects on both calcification and ERβ expression. E2 increased plaque calcification and decreased ERβ expression in the aortic sinus but not the innominate artery, in both male and female animals.…”
Section: Discussionmentioning
confidence: 74%
“…BMP2 may accelerate vascular calcification by increased phosphate uptake and inducing VSMCs phenotypes to convert into osteoblast‐like cells, which in turn phosphorylates the regulatory Smad1/5/8 and upregulates downstream key osteogenic transcription factors including Runx2 and Sp7 (osterix). In addition, upregulated Runx2 induces bone‐related matrix proteins, such as osteocalcin, type I collagen α1, and osteopontin . There is evidence that BMP2 is the target gene of Sp1 in the BMP2‐expressing F9 cell model system .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, upregulated Runx2 induces bone-related matrix proteins, such as osteocalcin, type I collagen a1, and osteopontin. [30][31][32][33][34] There is evidence that BMP2 is the target gene of Sp1 in the BMP2-expressing F9 cell model system. 18 Therefore, we analyzed the BMP2 sequence by using the Neural Network Promoter Prediction software to verify the binding site and found the Sp1 binding site, suggesting that Sp1 acts as a potential transcription factor for BMP2 activation.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have also suggested that besides ESRRA, ESRRG is also essential for cardiac metabolism and function, and plays an important role in the pathogenesis of cardiovascular diseases, such as cardiac hypertrophy, vascular calcification, heart failure, etc. [113,116,117]. Recently, a natural polyphenolic compound found in red wine, resveratrol, has been shown to improve high-fat diet-induced cardiomyopathy in mice in an ESRRA-dependent manner [118].…”
Section: Esrra As a Target For Cardiovascular Diseasesmentioning
confidence: 99%